Ample opportunities of GIS of technologies in dynamic mapping (Journal of Geography and Environmental Management, 2019)
The data on mapping development of technology allowing to receive new existential dynamic models,meeting the requirements of the becoming complicated scientific researches and daily arising practicaltasks are provided in article.